Synthesis and catalytic application of magnetic Co–Cu nanowires - Sun, Lijuan; Li, Xiaoyu; Xu, Zhiqiang; Xie, Kenan; Liao, Li (Beilstein Journal of Nanotechnology, 2017)
A rapid, template-free method was developed to prepare magnetic, bimetallic Co–Cu nanowires via liquid phase reduction and metal replacement under an external magnetic field. The characterization results confirmed that the as-prepared product was bimetallic Co–Cu nanowires with a desirable linear structure. Additionally, the magnetic hysteresis loop showed that the bimetallic Co–Cu nanowires were paramagnetic, which meant they could be easily separated from the reaction mixture. Furthermore, they were applied to the hydrolysis system of ammonia borane as a catalyst for the first time. More importantly, the catalysis results showed that the bimetallic nanowires possessed appealing catalytic performance. Therefore, a rapid and facile synthesis method is introduced which is capable of preparing bimetallic Co–Cu nanowires with great potential for industrial applications.
Keywords: catalyst; Co–Cu nanowires; liquid phase reduction; magnetic materials; metal replacement